Pemikiran Teologis Galatia 5:16 Dalam Perspektif Spiritual Leadership sebagai Solusi Pencegahan Kejatuhan Moral Pemimpin Rohani - Vivian, Elvan; Nugroho, Andreas Eko; Jonathans, Kornelius Rulli (Institut Agama Kristen Negeri Tarutung, 2024)
In recent decades, Christianity has been shaken by reports of moral failures among spiritual leaders. News of corruption, fraud, power struggles, and other scandals have flooded the media. However, the most shocking are the cases involving sexual misconduct by spiritual leaders. Churches and congregations have become victims of these leaders’ moral failures, resulting in shame, stress, depression, and even suicide among church members. Arising from this critical issue, the purpose of this study is to explore the theological insights of Galatians 5:16 and identify the solutions it offers. This research employs a library-based method, supported by interviews with two spiritual leaders and a hermeneutical analysis of Galatians 5:16. The findings reveal that walking by the Holy Spirit forms the foundation for ethical behavior among believers, especially spiritual leaders. Such ethical conduct can be actualized through consistent spiritual disciplines, which lead to four practical solutions for preventing moral failure.